Gasteric Emptying Study With Milk: Analysis in Children of Pakistan - Kareem, Abdul; Rehman, Adil; Ahmad, Awais; Mahmood, Nasir (Journal of Materials and Physical Sciences, 2023)
Gastro esophageal reflux (GER) is a widespread physiological phenomenon in children. In some children GER may be described as pathological and contribute to respiratory problems such as bronchial asthma and upper respiratory tract. The main objective of this study was to evaluate the presence of Gastro esophageal reflux disease (GERD) in children. Thirty children (up to 6 months of age) suspected with GERD were included in this study. The gastric emptying (SPECT) study was conducted according to predetermine protocol. All patients underwent Tc-99m DTPA gastric imaging for 30 minutes for children. The study was analyzed qualitatively i.e. visual analysis and quantitatively i.e. time activity curve (TAC) and Reflux index percentage (RI %) analysis for the presence of GER. The detection rate of GER in our study was 33% in children. This shows poor diagnoses of physicians because most of the children suffering from vomiting problems were diagnosed GERD but actually they were suffering from asthma and tonsillitis. The diagnosis and treatment of GER is mandatory in children asthma and tonsillitis. Gastric SPECT represents a significant advance in the diagnosis and quantitation of GER. It is one of the simplest radionuclide investigations which can be conducted with least patient inconvenience at a considerable low radiation burden. It can detect GERD with great accuracy even after physiologic neutral pH meal.